1992
DOI: 10.1099/00221287-138-10-2159
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the flagellin (hag) gene of alkalophilic Bacillus sp. C-125

Abstract: Motility of the alkalophilic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…This indicated that the central region of the leptospiral FlaB protein is highly variable in amino acid sequence and could be species specific. A similar sequence pattern was also found with other flagellins (25,29). The information contained in the central region may be useful for the design of a specific peptide or DNA probe to detect infection with leptospires.…”
supporting
confidence: 67%
“…This indicated that the central region of the leptospiral FlaB protein is highly variable in amino acid sequence and could be species specific. A similar sequence pattern was also found with other flagellins (25,29). The information contained in the central region may be useful for the design of a specific peptide or DNA probe to detect infection with leptospires.…”
supporting
confidence: 67%
“…The molecular mass of C. difficile flagellin, 39 kDa, is in the middle of the range of other characterized flagellin molecules, which have been reported to have molecular masses ranging from 15 to 62 kDa (Arnold et al, 1998 ;Joys, 1988 ;Sakamoto et al, 1992 ;Wilson & Beveridge, 1993). C. difficile flagellins did not display heterogeneity between the different strains studied nor did they have multiple molecular masses.…”
Section: Discussionmentioning
confidence: 88%
“…Prediction of antigenic determinants in FliC of C. difficile using the Hopp and Woods algorithm (Hopp & Woods, 1981) revealed the highest probability for the presence of such motifs in the central, variable region between aa 100 and 130. The central region has been proposed to be the region that is exposed to the outer environment (Sakamoto et al, 1992). Like other flagellins, the central portion has a surplus of acidic residues over basic residues and, by implication, a net negative charge.…”
Section: Discussionmentioning
confidence: 99%
“…DNA probes for sec Y (Kang et al 1992) and rpoA from strain C-125 hybridized to the same fragments 4A and 3S' ( Table 4). It was also found that probes for groEL (Xu et al 1996) and hag (Sakamoto et al 1992) hybridized to 3A and 4S, and llA and IS, respectively. 7).…”
Section: Mapping Of Genetic Locimentioning
confidence: 94%